Effects of connecting materials on the static and fatigue behavior of pultruded basalt fiber-reinforced polymer bolted joints. (1st March 2021) - Ding, Lining; Liu, Lulu; Wang, Xin; Shen, Haibin; Wu, Zhishen
Highlights: Design of homogeneous bolted joints with BFRP bolts. Comparable static behavior of bolted joints with BFRP bolts. Excellent fatigue behavior of bolted joints with BFRP bolts. Abstract: Owing to the heavy weight and poor durability of the bolted joints with traditional connecting materials composed of steel cover plates and steel bolts in the fiber-reinforced polymer (FRP) profiles, a novel homogenous joint consisted of basalt FRP (BFRP) cover plates and BFRP bolts was developed in this study. An experimental investigation on the static behavior of the double-lap shear bolted joints was carried out using different connecting materials to be compared, i.e. four types of combinations composed of steel/BFRP cover plates and steel/BFRP bolts, and different numbers of bolts. Fatigue experiments of the bolted joints with selected combinations were performed to further compare the behavior of the homogenous joints using S - N curve and fatigue strength. The results showed that shear-out failure occurred in the inner plates in all bolted joint combinations, which was independent of the connecting material. The ultimate failure load of the homogeneous joints was comparable to that with the traditional connecting material. However, the fatigue strength level for the specimens sustaining more than 2 million cycles for the former was slightly higher than the latter with same stress ratio of 0.05. The predicted stress level as a function of the fatigue lives was obtained from the experimental results showing satisfactory regression. The experimental work can serve as a reference in the design of FRP bolted joints applied in the truss structures.